Implementasi layanan pinjam meminjam perbankan syariah berbasis peer to peer lending guna mewujudkan sharia compliance - Imro'ah, Wulidatul (Maliki Interdisciplinary Journal, 2024)
Islamic banking, which is governed by Islamic sharia principles, combines financial technology through peer to peer Islamic lending as a new approach to lending services. The platform is designed to connect lenders and borrowers via the internet, facilitating a faster process for the community. However, this convenience has sparked significant criticism regarding the compliance with sharia principles in peer to peer Islamic lending, which is considered less compliant in Indonesia. The purpose of this study is to explore the concept of implementing peer to peer Islamic lending and to examine the implementation and supervision of sharia compliance in Islamic banking. A qualitative descriptive research method was used, utilizing a literature review to uncover themes or discussions from previous books, articles, and research journals. The findings provide an overview of the mechanisms involved in peer to peer Islamic lending-based financial technology services, detailing the procedures carried out by lenders and borrowers, as well as the implementation and monitoring of sharia compliance in Islamic banking as a demonstration of compliance with sharia principles.